1981
DOI: 10.1210/jcem-53-6-1193
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Hormonal Characterization of Cryptic 21-Hydroxylase Deficiency*

Abstract: Cryptic 21-hydroxylase deficiency has been previously described in asymptomatic family members of patients with classical congenital adrenal hyperplasia (CAH). These family members were detected by high baseline 17-hydroxyprogesterone levels found in the course of family studies. The hormonal responses to ACTH of the family members with cryptic 21-hydroxylase deficiency were determined and compared to the responses of patients with CAH, patients with acquired adrenal hyperplasia, family members predicted to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
12
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(16 citation statements)
references
References 0 publications
4
12
0
Order By: Relevance
“…The LO form may be either symptomatic, causing virilization in late childhood or at puberty, or asymptomatic. The latter, also called the cryptic form, was initially described in families with the classic form, the authors suggested that the asymptomatic patients were compound heterozygotes for a classic and a cryptogenic gene (Levine et al 1981;Levine and Pang 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The LO form may be either symptomatic, causing virilization in late childhood or at puberty, or asymptomatic. The latter, also called the cryptic form, was initially described in families with the classic form, the authors suggested that the asymptomatic patients were compound heterozygotes for a classic and a cryptogenic gene (Levine et al 1981;Levine and Pang 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Steroid 21-hydroxylase deficiency accounts for 90 -95% of CAH cases (1,2). The symptoms of steroid 21-hydroxylase deficiency are classified into three distinct clinical phenotypes: the salt-wasting (SW), simple virilizing (SV), and nonclassical (NC) forms (1)(2)(3)(4)(5)(6)(7). SW and SV forms of steroid 21-hydroxylase deficiency produce masculinization of the external genitalia in girls and, therefore, can be detected at birth in girls by careful examination of the external genitalia.…”
mentioning
confidence: 99%
“…The NC form presents later in life as premature pubarche, hirsutism, acne, or menstrual abnormalities. The NC form may also be cryptic, which denotes asymptomatic individuals with the identical biochemical and genetic abnormalities as family members with the symptomatic NC form (2,3,(5)(6)(7).…”
mentioning
confidence: 99%
“…According to genotype, the predicted phenotype of case 2 is the more severe classic type [19,20]. These discrepancies between genotype and phenotype are often observed in nonclassical 21-OHD [18], the precise reason for this has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%